2020
DOI: 10.1186/s13054-020-03270-1
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study for the clinical application of extracorporeal membrane oxygenation in Mainland China, 2018

Abstract: Background To investigate the epidemiology and in-hospital mortality of veno-venous (VV) and veno-arterial (VA) extracorporeal membrane oxygenation (ECMO) in Mainland China throughout 2018. Methods Patients supported by ECMO from 1700 tertiary hospitals in 31 provinces from January 1 to December 31, 2018, were selected from the National Clinical Improvement System database. Results The 1700 included hospitals had 2073 cases of ECMO in 2018, including 714 VV and 1359 VA ECMOs. The average patient age was 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Yang et al ( 7 ) found that EMCO might be effective for these patients, but the sample size was small. Schmidt et al ( 8 ) found the estimated 60-day survival of these patients were similar to that of recent studies ( 5 , 9 ) and ECMO was recommended for severe ARDS associated with COVID-19 patients. However, several important key factors need to be mentioned.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Yang et al ( 7 ) found that EMCO might be effective for these patients, but the sample size was small. Schmidt et al ( 8 ) found the estimated 60-day survival of these patients were similar to that of recent studies ( 5 , 9 ) and ECMO was recommended for severe ARDS associated with COVID-19 patients. However, several important key factors need to be mentioned.…”
Section: Introductionsupporting
confidence: 73%
“…Our research team recently found that the overall survival rate of ECMO patients in Mainland China was up to the level of developed countries ( 9 ). But overall in-hospital mortality of ECMO supported COVID-19 patients appeared considerably higher than that in a recent series by Schmidt, although 28-day mortality rate was similar ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, nosocomial infection in patients supported by ECMO is highly likely to result in the death, which can cause significant underestimation of the hospital expenses due to nosocomial infection (28). Secondly, some studies have found that prophylactic antibiotics during ECMO could reduce nosocomial infection and showed lower mortality (29,30). Therefore, medical institutions usually increase the use of antibiotics in order to save lives for patients who need ECMO support, no matter whether nosocomial infection occurs or not, which can be reflected from the no statistically significant difference in the use of prophylactic antibiotics and the cost of antibiotics between ECMO infection group and ECMO non infection group.…”
Section: Discussionmentioning
confidence: 99%
“…However, we classified the ECMO survivors considering the main diagnosis at ECMO therapy into the cardiovascular group, respiratory group, and other group. In a recent cohort study, patients who underwent ECMO therapy with a primary diagnosis of acute respiratory failure constituted the VV-ECMO group, while patients who underwent ECMO therapy with a primary diagnosis of cardiogenic shock or cardiac arrest constituted the VA-ECMO group [ 34 ]. Thus, our classification using main diagnosis at ECMO therapy might provide some important information for readers on the effect of type of ECMO.…”
Section: Discussionmentioning
confidence: 99%